Biographical Files
This series consists of press clippings, news agency releases and RFE/RL research papers and monitoring materials. The documents give information on about 5500 prominent and less prominent Hungarian state, opposition or dissident politicians, writers, actors, journalists and other public figures. Occasionally, speeches and publications by them are also included. Of outstanding interest are the files on leading personalities and martyrs of the 1956 Hungarian Revolution (Imre Nagy, Pál Maléter, József Mindszenty), opposition figures of the Kadar-regime, and the highest level communist party leaders (György Aczél, Béla Biszku, János Kádár, Zoltán Komócsin). Accruals not expected